Looking at Dependence: Vulnerability and Power in the Gospel of the Foot Washing - Cooreman-Guittin, Talitha (Journal of disability & religion, 2021)
Accepting help of other people does not always come natural to us. On the contrary, it is often felt as degrading and even indignant. Yet, dependence is an essential characteristic of human life. It has been inscribed in the opening pages of the Bible that humanity is dependent and at the same time fully in God’s image. The biblical narrative frequently recalls that it is only in relationships of care and mutual help that we can encounter God. This dependence on other human beings, so complicated to live with, is also highlighted in a singularly empowering way by Jesus in the dusk of his life, when he washed the feet of his disciples. This contribution shows how several biblical passages illuminate dependence and vulnerability as places of empowerment and as part of God's plan for humanity.